Determinan Audit Delay (Studi Kasus Pada Tiga Perusahaan IDX30 Periode 2020–2023) - Isma Juliana; Nur Fitriyah (Fakultas Ekonomi dan Bisnis Unram, 2026)
The purpose of this study is to analyze the impact of profitability, leverage, liquidity, firm size, and firm age on audit delay among companies listed in the IDX30 index during the 2020–2023 period. Audit delay refers to the delay in the submission of audited annual financial statements. The sampling method employed purposive sampling, resulting in three major companies that were consistently listed in the IDX30 index and experienced audit delay during the research period, namely PT Charoen Pokphand Indonesia Tbk (CPIN), PT Perusahaan Gas Negara Tbk (PGAS), and PT Telekomunikasi Indonesia Tbk (TLKM), with a total sample of 12 firm-year observations. The results indicate that profitability, leverage, and liquidity do not have an impact on audit delay. Meanwhile, firm size and firm age have an impact on audit delay.